Peran Guru Sekolah Dasar dalam Mewujudkan Pendidikan Berkualitas Sebagai Upaya Mendukung Sustainable Development Goals (SDGS) di Indonesia - Permata Fayzah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Quality education is one of the 17 global goals known as the Sustainable Development Goals (SDGs), particularly Goal 4. This goal aims to ensure equitable, inclusive, and quality education for all people. In Indonesia, elementary school teachers play the most important role because they interact directly with students every day. This article comprehensively examines the role of elementary school teachers in supporting SDG 4 from three main perspectives: teachers’ professional competence, innovative teaching methods, and teachers’ involvement within the school community. The method used is a systematic review of 45 selected scientific sources published between 2020 and 2024, including international journals, reports from global institutions, and Indonesian government policy documents.The findings show that competent, creative, and highly dedicated elementary school teachers are closely related to improving learning quality, increasing school participation, and developing positive character in students. However, several major challenges remain unresolved, such as unequal teacher distribution, low welfare, and limited access to technology—especially in remote areas. This article recommends three main actions: strengthening continuous teacher professional development policies, improving the teacher performance evaluation system to make it more comprehensive, and increasing collaboration among the government, universities, and local communities in order to achieve SDG 4 effectively in Indonesia.